The shaping of ambient intelligence and the internet of things : historico-epistemic, socio-cultural, politico-institutional and eco-environmental dimensions /: historico-epistemic, socio-cultural, politico-institutional and eco-environmental dimensions. (2015) - Bibri, Simon Elias
No abstract available